(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, continuous spiritual education means that the student’s consciousness is related to society, that he has a duty to society, that he understands that his behavior depends on the level of development of society, that he feels responsibility in fulfilling the moral standards, ideals and requirements recognized by society. Opinions about the need to turn spiritual and moral knowledge into beliefs and the systematicity of these beliefs, the formation of strong spiritual and moral feelings and traits are stated..